(untitled) (Sociologisk Forskning, 1994)
Lifeworlds and Systemtransformations How are we to understand and explain the ongoing processes of transformation in Eastern Europe? The main thesis of this article is that the difficulties of the social sciences to predict both the collapse of the previous system and the difficulties in transforming them to systems of the Western type, is due to an underestimation of the strength and independence of the life-world dimension of the social order. The predominance of ”systemic thought” in the social sciences is related to a view of capitalism which grossly overestimates the unpersonal, ”systemic” dimension of this social order. It is argued that the capitalist social order is not only a system, but is also contingent on the existence of a life-world. The coming into existence of this life-world cannot be taken for granted. Sociology has partly recognized the existence of this life-world by emphasizing the importance of the moral dimension in capitalist societies, but theoretically and methodologically ”systemic” sociology has been unable to explain how this particular capitalist morality is possible. The role of Adam Smiths theory of morality and capitalism is discussed and compared to other, more ”life-world”-oriented sociological theories, such as phenonemology, the symbolic interactionism of Cooley and Mead, and the civilizational sociology of Norbert Elias.